Pengaruh Pemberian Kombinasi Jus Buah Pepaya Dan Serbuk Daun Kelor Terhadap Kadar Hemoglobin Ibu Hamil - Trinumasari, Aris; Pramono, Joko Sapto; Suryani, Heni (Bunda Edu-Midwifery Journal (BEMJ), 2023)
In addition to taking FE tablets, one of the efforts to prevent anemia is to eat fruits rich in vitamin C and iron, namely papaya and Moringa leaf powder. The aim of the study was to determine the effect of a combination of papaya fruit juice and moringa leaf powder on the hemoglobin levels of pregnant women. This research method is semi-empirical with pre-test and post-test with control group design. The population of this study included all pregnant women in the 2nd and 3rd trimesters of the UPTD Muara Kaman Center for Public Health Ulu Village UPTD Muara Kaman. Sampling technique was used for purposeful sampling of 36 people. The results of this study show that there is an effect of a combination of papaya fruit juice and moringa leaf powder on the hemoglobin levels of pregnant women with P-Value: 0.000 less than α: 0.05.. There was a significant difference in mean hemoglobin concentration between the control group and the intervention group with sig. (2-taliled): 0.025 less than α : 0.05.. The iron needed by pregnant women cannot be properly absorbed by the body because the mother lacks vitamin C, so the body really needs more vitamin C to help with the absorption or absorption of iron in the body. Effect of a combination of papaya juice and Moringa leaf powder on hemoglobin levels of pregnant women